Success Factors in Ethiopian Premier League Soccer Clubs in 2023/24 - Getnet, Daniel; Melkamu, Zelalem; Mengistu, Sisay (Indonesian Journal of Sport Management, 2025)
Soccer is one of the most globally recognized and profitable industries in the entertainment sector. Knowledge of the success factors of professional soccer is critical. However, in the literature, the identification of success factors has primarily focused on the Big Five, which is not inclusive. This study examines the key factors that drive club performance in the Ethiopian Premier League (EPL) during the 2023/24 season, with the main goal of identifying and categorizing these factors using Explanatory Factor Analysis (EFA). Employing a quantitative, cross-sectional research design, was collected from 307 players, and systematically sampled from a population of 354 across all EPL clubs. The study was conducted by ethical guidelines and was approved by the Research Ethics Review Committee of Hawassa University College of Natural and Computational Sciences Research Ethics Review Committee. A 36-item self-administered survey, developed and validated by expert panels, and piloted with 90 objective groups before use. The Kaiser-Meyer-Olkin (KMO) value of.819 and Bartlett’s Test of Sphericity confirmed the appropriateness of the data for factor analysis. Principal Component Analysis (PCA) identified eight key components that influence club success, including fan engagement, financial management, leadership, and human capital. Results show that fan support and media presence significantly impact club performance, while financial stability and strong leadership are crucial for operational success. Additionally, a club’s history and culture contribute to fostering loyalty and sustained performance. Moreover, eight factors accounted for 75.76% of the variance, which is (27.17%, 14.27%, 8.67%, 7.08%, 6.08%, 4.539%, 3.97%, and 3.24).  However, 23% of the variance in club success remains unexplained, suggesting that other factors are at play. In conclusion, success in the EPL is shaped by a combination of internal and external factors, including fan engagement, financial practices, leadership, and team depth.